Suppressor cell induction in vitro. III. Antigen-specific suppression by supernatants of suppressor cells. - Kontianinen, S; Feldmann, M (1977)
Antigen-specific suppressor T cells induced in vitro release, after a further period of culture in vitro with antigen factors into the supernatant which have suppressor activity. These suppressor factors (SF) have the same antigen specificity as the suppressor cells (SC). SF only works on the early phase of thymus-dependent responses in cultures. SF inhibits thymusdependent IgM, but not thymus-independent IgM responses in vitro. SF is is destroyed by proteolytic enzymes, and inactivated at 80 degrees C for 30 min. The release of SF from SC is dependent on the presence of antigen and metabolically active cells.